2008
DOI: 10.1073/pnas.0801868105
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of established cancer using a histone deacetylase inhibitor and a TRAIL receptor agonist

Abstract: Histone deacetylase inhibitors (HDACi) and agents such as recombinant tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) and agonistic anti-TRAIL receptor (TRAIL-R) antibodies are anticancer agents that have shown promise in preclinical settings and in early phase clinical trials as monotherapies. Although HDACi and activators of the TRAIL pathway have different molecular targets and mechanisms of action, they share the ability to induce tumor cell-selective apoptosis. The ability of HDACi to indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 34 publications
(50 reference statements)
5
99
0
Order By: Relevance
“…Although a number of studies have shown that HDAC inhibitor-mediated downregulation of FLIP sensitises various cancer cell lines to death ligands, such as TRAIL, 23,27,28 to our knowledge, no previous studies have directly examined whether FLIP downregulation is a sufficient death signal for apoptosis induction when these agents are administered as single agents. We found that FLIP downregulation in response to HDAC inhibitors results in caspase 8-and DR5-mediated apoptosis, phenocopying the mechanism of apoptosis that we previously observed in CRC cells following siRNA-mediated downregulation of FLIP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of studies have shown that HDAC inhibitor-mediated downregulation of FLIP sensitises various cancer cell lines to death ligands, such as TRAIL, 23,27,28 to our knowledge, no previous studies have directly examined whether FLIP downregulation is a sufficient death signal for apoptosis induction when these agents are administered as single agents. We found that FLIP downregulation in response to HDAC inhibitors results in caspase 8-and DR5-mediated apoptosis, phenocopying the mechanism of apoptosis that we previously observed in CRC cells following siRNA-mediated downregulation of FLIP.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings agree with a recent study in breast cancer models, which also found that SAHA-induced FLIP downregulation was post-transcriptional. 23 In addition, a related pan-HDAC inhibitor Panobinostat (LBH589) was recently reported to cause FLIP polyubiquitination and proteasomal degradation in pancreatic cancer cells. 24 Collectively, these findings suggest that SAHA causes Ku70 acetylation, resulting in the disruption of its interaction with FLIP leading to degradation of FLIP by the UPS.…”
Section: Discussionmentioning
confidence: 99%
“…Similar protection from chemotherapeutic drug-induced apoptosis can be afforded by overexpression of any of the other prosurvival BCL-2 family members. [134][135][136][137] Studies using gene-targeted mice or RNAi-mediated gene knockdown in cell lines revealed which pro-apoptotic BCL-2 family members are critical for cell killing by which anticancer agent. Consistent with the notion that BAX and BAK have essential overlapping functions in the BCL-2-regulated apoptotic pathway, cells from Bax −/− Bak −/− mice are markedly resistant to diverse anticancer agents.…”
Section: The Role Of the Bcl-2-regulated Apoptotic Pathway In Cancer mentioning
confidence: 99%
“…To overcome this resistance, TRAIL-induced signaling is being studied alone or in combination with different sensitizing agents, such as chemotherapeutic drugs, cytokines and inhibitors of survival pathways [4][5][6].…”
Section: Introductionmentioning
confidence: 99%